Giant Non-traumatic Splenic Pseudocyst Mimicking a Pancreatic Pseudocyst: A Case Report - Priya Dharshini Rajaram; Ramidi Yeshwanth Reddy; Jasvant Ram Ananthasayanam; Paarthipan Natarajan (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Splenic pseudocysts are rare non-parasitic cystic lesions of the spleen characterised by the absence of an epithelial lining. Most occur following trauma, whereas non-traumatic splenic pseudocysts are uncommon. A 45-year-old woman presented with a one-year history of chronic postprandial vomiting, early satiety, abdominal fullness, weight loss (6-7 kg), and recent-onset breathlessness. Initial ultrasonography suggested a pancreatic pseudocyst because of the apparent proximity of the lesion to the pancreatic tail and poor visualisation of the spleen. However, normal serum amylase and lipase levels together with unexplained cytopenias prompted further evaluation. Contrast-Enhanced Computed Tomography (CECT) revealed a large splenic cystic lesion with peripheral calcifications and internal septations, establishing its splenic origin and prompting revision of the initial diagnosis of pancreatic pseudocyst. The patient subsequently underwent open splenectomy. Histopathological examination confirmed a splenic pseudocyst. This case highlights that a presumed pancreatic pseudocyst in the absence of pancreatitis and with normal serum amylase and lipase levels should prompt consideration of alternative diagnoses, including splenic pseudocyst.